2015
DOI: 10.1093/jxb/erv255
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, localization, and seasonal changes of the sucrose transporter FeSUT1 in the phloem ofFraxinus excelsior

Abstract: HighlightIn Fraxinus excelsior the sucrose transporter FeSUT1 is located in the phloem and involved in apoplastic sucrose loading and retrieval. The expression of FeSUT1 is higher under low sucrose conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Some of these clones have been shown to be functional SUTs by expressing them in Xenopus oocytes or yeast (Deol et al, 2013; Oner-Sieben et al, 2015; Zanon et al, 2015), but their ability to regulate plant metabolism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these clones have been shown to be functional SUTs by expressing them in Xenopus oocytes or yeast (Deol et al, 2013; Oner-Sieben et al, 2015; Zanon et al, 2015), but their ability to regulate plant metabolism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Early structural evidence suggested that ICs and OCCs were found in the minor veins of cucurbits (Turgeon et al ., ; Schmitz et al ., ; Rennie and Turgeon, ). In some other species, for instance, Asarina barclaiana and Acanthus mollis contained TCs and ICs (Voitsekhovskaja et al ., ), while Amborella trichopoda and Fraxinus excelsior included OCCs and ICs (Fu et al ., ; Öner‐Sieben et al ., ) in the minor veins. These phenomena suggest that apoplastic and polymer‐trapping mechanisms are probably at work in individual cells of the same veins.…”
Section: Discussionmentioning
confidence: 94%
“…It has also been found that some plants, such as Alonsoa meridionalis and Amborella trichopoda , could employ both polymer‐trapping and apoplastic loading mechanisms based on the presence of ICs and ordinary companion cells (OCCs) in the minor veins (Knop et al ., ; Voitsekhovskaja et al ., ; Turgeon and Medville, ). For Fraxinus excelsior , a RFOs‐transporting species, FeSUT1 was found and localized in SEs and possibly in OCCs of minor veins (Öner‐Sieben and Lohaus, ; Öner‐Sieben et al ., ). In the same veins of Amborella, a stachyose synthase gene, AmSTS1, was expressed in ICs but not in OCCs in which the sucrose transporter (AmSUT1) was expressed (Voitsekhovskaja et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…While concerns have been raised regarding the accuracy of the different methods used to investigate sugar concentrations (see discussion in Reidel et al and Öner‐Sieben and Lohaus ), measurement errors are unlikely to explain the massive concentration difference between phloem and mesophyll observed in species like Q. robur (Öner‐Sieben and Lohaus ). It has been speculated that either the respective PD are closed and the plants under study use active apoplasmic loading, as in herbs, or these species represent a mixed loading type (Öner‐Sieben et al, ).…”
Section: Discrepancy In Classification and Potential For Mixed Loadinmentioning
confidence: 99%